Parental Rights and Obligations to Children in the Era of Industrial Revolution 4.0 (Islamic Family Law perspective) - Asman, Asman (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2020)
In accordance with the current development of the current era of globalization is very fast developing, especially digital technology called the era of revolution Industry 4.0 where the existence of technology and information can be accessed anytime and by anyone, so that positive and negative impacts on the rights and obligations of parents to children in the family. This study uses a qualitative approach by collecting data through library research techniques, then analyzed in the perspective of Islamic family law. The method used is descriptive qualitative which describes data related to the rights and obligations of parents to children in the revolutionary 4.0 era in the perspective of Islamic family law. The focus of the problem in this study is how the rights and obligations of parents towards children in the 4.0 revolution industry era in the perspective of Islamic family law. The results of this study, parents have rights and obligations which are the responsibility of actualizing the rights of children in protecting, controlling, educating, maintaining respect and protecting children in the family.